Infecticode: The Molecular Lockdown - unlocking molecular mysteries through an educational escape room - Mohamed, Suwaibah; Kamarudin, Ammar Akram; Shamsusah, Nadia Aqilla; Ismail, Norul Fadhilah; Zainal-Abidin, Nurhamimah (2025)
Systematic bacteriology is often seen as difficult and complex, leading to low student engagement and limited conceptual understanding. InfectiCode: The Molecular Lockdown was developed as an innovative escape room-style educational game using the Genial.ly platform. The game is set in a hospital outbreak scenario, in which participants assume the role of a clinical investigation team responsible for identifying the pathogen causing neonatal sepsis in a newborn. Clues are gathered through a series of guided tasks incorporating phenotyping and genotyping principles, to unlock a briefcase containing a reward. A pre-test and post-test using similar questions were given to evaluate the students' understanding, and a satisfaction survey form was administered to capture perceptions related to engagement and the learning experience. The Wilcoxon signed-rank test was performed to determine statistical differences in scores obtained before and after the game was conducted (p-value <0.05). The results indicated significant improvements in understanding and high satisfaction levels regarding the game design and delivery. This game-based approach provided an effective alternative to conventional teaching methods by promoting deeper conceptual learning, collaboration, and learner motivation. Importantly, the simulation also fosters anticipatory thinking, one of the core competencies of Education for Sustainable Development, by encouraging learners to envision future public health systematic bacteriology. The outcomes suggest that game-based learning can help students learn complex scientific content more enjoyably and effectively.